IDENTITY OF LATVIAN AND LITHUANIAN CITIES ON THE BALTIC SEASHORE - Ozola, Silvija (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2018)
The Baltic seashore cities Liepaja, Ventspils and Palanga people’s relationships with the sea had an impact on architectural quality of surrounding, which reflect understanding of the economic, culture and art. One of the sustainable development preconditions is identity, which can be achieved by identification, preservation and restoration of cultural heritage, natural objects and specific landscape. Identity of city environment is formed by cultural heritage that encodes information about many processes in the past. There is limited knowledge of the identity of coastal cities in the Baltic countries, where living environment is rich with forms and structures, which can satisfy individual's physical and mental needs, and inspire new ideas. To realize sustainable and balanced development of the Baltic seashore cities Liepaja, Ventspils and Palanga, structural changes are carried out using different spatial development models.The goal of this research is to compare models of sustainable spatial development of the Baltic seashore Latvian cities Liepaja and Ventspils, as well as Lithuanian city Palanga, and to assess their effects on the citizen quality of life.